Pandanus amaryllifolius leaf extract increases insulin sensitivity in high-fat diet-induced obese mice - Suphaket Saenthaweesuk; Jarinyaporn Naowaboot; Nuntiya Somparn (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To examine the effect of Pandanus amaryllifolius (P. amaryllifolius) leaf extract on the insulin resistance state in obese ICR mice. Methods: Obesity was induced in mice fed with high-fat diet (45% fat) for 12 weeks. After the first six weeks on the diet, the obese mice were administered with the water extract of P. amaryllifolius leaf at 125 and 250 mg/kg/day, respectively for another six weeks. At the 5th week of treatment, oral glucose tolerance test was conducted. After six weeks of treatment, the levels of blood glucose, serum insulin, leptin, adiponectin, and lipid profiles were determined. The liver, muscle and epididymal fat tissues were removed for measuring the biochemical parameters and protein expression, as well as histological examination. Results: Six weeks of treatment with P. amaryllifolius led to a significant reduction in the blood glucose level as well as improvement in the insulin resistance. P. amaryllifolius also increased the liver glycogen storage and serum adiponectin and decreased the serum leptin levels. A reduction in the serum and hepatic triglyceride, and non-esterified fatty acid levels was also observed. The histological examination showed that the obese mice treated with P. amaryllifolius reduced the lipid droplet in liver tissue and adipocyte size in epididymal fat tissue. The treatment also increased the protein expression of glucose transporter 4 in the muscle and fat tissues. Conclusions: The treatment with P. amaryllifolius could decrease several parameters of impaired glucose and lipid metabolism. To the best of our knowledge, this is the first report on the role of P. amaryllifolius leaf extract in alleviating the insulin dysfunction in obesity state.